The The Use of Transition Signals in University Students’ Community Service Report - Ni Putu Cahyani Putri Utami; Made Wahyu Mahendra (Yavana Bhasha : Journal of English Language Education, 2021)
Transition signals are the essential elements to achieve a well-structured text. Theideas in the text need to connect to each other. It will be difficult for the reader tounderstand the sequence if the ideas are simply just exposed by the writer without beingrelated to each other. Students’ competency and ability in English academic writingoverviewed from their competence in constructing sentences. Therefore, this researchaimed to find out the use of transition signals and their accuracy in students’ communityservice report. The research used a descriptive quantitative method. The data were takenfrom students’ community service report written by the seventh semester Englishliterature students of Foreign Languages Study Program of Universitas MahasaraswatiDenpasar. The finding of this research showed that the total number of transition signalsused by the students in their community service report were 303 and classified into eighttypes of transition signals. Transition signals to introduce sequence and logically orderideas was mostly used and transition signals to emphasize ideas was least used by thestudents. From the whole types of transition signals, the average usage accuracy wasabove 60%.Keywords: t